Call and Connections Times in ASON/GMPLS Architecture - Młynarczuk, Magdalena; Zieńko, Paweł; Kaczmarek, Sylwester (Journal of Telecommunications and Information Technology, 2013)
It is assumed that demands of information society could be satisfied by architecture ASON/GMPLS comprehended as Automatically Switched Optical Network (ASON) with Generalized Multi-Protocol Label Switching (GMPLS) protocols. Introduction this solution must be preceded by performance evaluation to guarantee society expectations. Call and connections times are in ASON/GMPLS architecture important for real-time applications. Practical realization is expensive and simulations models are necessary to examine standardized propositions. This paper is devoted to the simulation results of ASON/GMPLS architecture control plane functions in OMNeT++ discrete event simulator. The authors make an effort to explore call/connection set-up times, connection release times in a single domain of ASON/GMPLS architecture.
Keywords: ASON; call control; call time; connection control; connection time; GMPLS; simulation model